ANALISIS HUKUM ISLAM TERHADAP JUAL BELI TANPA LEBEL HARGA - Yunita Yunita; Meydi Lestari (Jurnal At-Tabayyun, 2022)
This study aims to analyze Islamic law on buying and selling without a price tag. The practice of buying and selling without price tags often occurs in various economic contexts, where the price of goods or services is determined directly or through bargaining between buyers and sellers, without clear pricing. This research was conducted using a qualitative approach and literature study methods to collect data from related literature, such as books on Islamic law, reference books, and scientific articles. In this study, the views of Islamic law are analyzed regarding the practice of buying and selling without a price tag. The principles of Islamic law relating to economic transactions, such as fairness, transparency, mutual pleasure between buyers and sellers, and the avoidance of fraud and injustice, are the focus of this analysis. Official documents, including fatwas from religious institutions, are also analyzed to obtain legal guidance relevant to this practice. The results of the analysis show that buying and selling without a price tag raises various legal issues in the context of Islamic law. Although there is no direct prohibition in the Qur'an or Hadith regarding this practice, the principles of Islamic law demand clear and fair pricing in economic transactions. In addition, non-transparency in pricing can result in losses and injustice for consumers. This study also emphasizes the need for a hermeneutical approach in understanding Islamic legal texts related to buying and selling. Through this approach, the historical context and meaning of Islamic legal texts can be better analyzed, and their relationship with contemporary realities can be considered in making relevant conclusions.